A Comparison Study of Indonesia and China: Macroeconomics Performance and Bank Soundness Performance - Maria Christina Liem; Peng Tze (JAAF (Journal of Applied Accounting and Finance), 2017)
The purpose of this study is to analyse the impact of macroeconomics performance towards bank soundness performance of state-owned commercial banks in Indonesia and China during 2014-2015. Indonesia and China are predicted to have crucial roles in global financial leader in the future due to huge population and recent financial performance. This study will compare macroeconomics performance and state-owned commercial banks’ soundness performance between Indonesia and China. The findings show that even though China has better macroeconomics performance compared with Indonesia, but state-owned commercial banks in China have worse performance in term of management performance and earnings performance compared with state-owned commercial banks in Indonesia. Furthermore, this study implements data panel GLS regression – random effect by STATA. As Casu et al (2009) mention that macroeconomics performance has positive impacts towards bank soundness performance, therefore this study analyse the impact of macroeconomics performance towards the bank soundness performance with unit analysis of state-owned commercial banks in Indonesia and China. The statistics results show that GDP growth rate has negative impact towards bank soundness performance, and interest rate has positive impact towards bank soundness performance. However, the inflation of consumer price has positive impact towards management performance and earning performance; and it has negative impact towards capital performance, asset performance, and liquidity performance. In short, this study shows that higher macroeconomics performance would not guarantee that state-owned commercial banks will have higher bank soundness performance as well.